At home in the law : how the domestic violence revolution is transforming privacy - Suk, Jeannie (Yale University Press, 2009)
In the past forty years, the idea of home, which is central to how the law conceives of crime, punishment, and privacy, has changed radically. Legal scholar Jeannie Suk shows how the legitimate goal of legal feminists to protect women from domestic abuse has led to a new and unexpected set of legal practices.Suk examines case studies of major legal developments in contemporary American law pertaining to domestic violence, self-defense, privacy, sexual autonomy, and property in order to illuminate the changing relation between home and the law. She argues that the growing legal vision that has led to the breakdown of traditional boundaries between public and private space is resulting in a substantial reduction of autonomy and privacy for both women and men.